DINAMIKA HUKUM ISLAM ‎: (Studi Pemikiran Ahl Al-Hadis dan Ahl Al-Ra'yi)‎ - Ahmad Farhan Subhi; M. Hasbi Umar; Ramlah (Jurnal Indragiri Penelitian Multidisiplin, 2023)
Islamic law has two characteristics, namely al-tsabat (fixed) and al-tathawwur (developing). The first characteristic, namely Islamic Law as a revelation of Allah which remains and does not change throughout time, while the second characteristic, namely Islamic Law which develops, is not rigid in various social situations and conditions. It is in the integration of these two characteristics that Islamic Law can last forever. The first characteristic is called sharia. While the second trait is called fiqh, namely the understanding of sharia. The division of the ulema into two major sects, Ahl al-Hadith and Ahl al-Ra'yi raises various kinds of legal issues and the results of ijtihad. This research focuses on discussing the history of the development of Ahl al-Hadith and Ahl al-Ra'yi, the influence of these two schools of thought on Islamic Law, and the style of thought of the two Imams of Schools (Maliki and Hanafi). This study uses a qualitative descriptive method and is a type of library research. This research finds two forms of thought in Islamic law from Ahl al-Ra'yi and Ahl al-hadith which have succeeded in making many contributions to the creation of legal foundations in the well-known schools of Islamic law which were built by each imam. his school. Most of the differences of opinion among the Imams of the Madhhab in establishing law are based on differences in viewing the foundations that exist in Islamic law. This research finds two forms of Islamic law thought from Ahl al-Ra'yi and Ahl al-hadith which have succeeded in making many contributions to the creation of legal foundations in the well-known schools of Islamic law which were built by each imam. his school. Most of the differences of opinion among the Imams of the Madzhab in establishing law are based on differences in viewing the foundations that exist in Islamic law. This research finds two forms of Islamic law thought from Ahl al-Ra'yi and Ahl al-hadith which have succeeded in making many contributions to the creation of legal foundations in the well-known schools of Islamic law which were built by each imam. his school. Most of the differences of opinion among the Imams of the Madzhab in establishing law are based on differences in viewing the foundations that exist in Islamic law.